Errors in Spoken Production Made by Students in Microteaching Class of Department of English Education of Muhammadiyah University of Surakarta in 2013/2014 Academic Year - Rahma, Hendita Leila, Prof. Dr. Endang Fauziati, M.Hum, Nur Hidayat S.Pd., M.Pd (2015)
This is descriptive qualitative research. It aims to describe the types of speech errors made by students, to describe the frequency of speech error made by students, and to describe the dominant error found in the microteaching class made by students, to explain the source of error made by students in microteaching class of Department of English Education. In collecting data, the writer watches, observes then writes the scripts of the videos of microteaching class. The writer uses theory of Clark and Clark to analyze speech error and found seven types of them, namely: filled pause, silent pause, repeats, correction, stutter, unretraced false start and retraced false start. From the data, the researcher found 447 error utterances that consist of 310 utterances or 69,35% of speech error, 91 utterances or 20,36% of morphological error and 46 utterances or 10,29% of syntactical error. The writer found 76 utterances or 17% of silent pause, 141 utterances or 31,54% of filled pause, 48 utterances or 10,74% of repeats, 8 utterances or 1,79% of correction, 7 utterances or 1,57% of stutters, 8 utterances or 1,79% of unretraced false start, 22 utterances or 4,92% of retraced false start, 61 utterances or 13,65% of vocabulary error, 30 utterances or 6,71% of error in the selection of word, 34 utterances or 7,61% of omissions of bound morpheme, 8 utterances or 1,79% of additions of bound morpheme, and 4 utterances or 0,89% of omission of to be. The writer also found two sources that make the utterances become error. The first is cognitive reason where the speakers need brain processing where information is processed to utter by speech. The second is psychological reason that happens when the speakers feel anxious, nervous, in hurry or other that can affect the speakers to be confident or un-confident that makes them difficult to produce speech.